P53, MAPK, topoisomerase II alpha and Ki67 immunohistochemical expression and KRAS/BRAF mutation in ovarian serous carcinomas - Sundov Dinka; Caric Ana; Mrklic Ivana; Gugic Dijana; Capkun Vesna; Hofman Irena Drmic; Mise Branka Petric; Tomic Snjezana (BMC, 2013)
Abstract Background We investigated the immunohistochemical expression of p53, MAPK, topoisomerase II alpha (topoII alpha) and Ki67 in ovarian serous carcinomas (OSCs) along with mutational analysis for KRAS and BRAF. Methods Eighty one cases of OSCs were reviewed and examined immunohistochemically using antibodies against p53, MAPK, topoII alpha and Ki67. Staining was evaluated as a percentage of immunopositive cells with cut-off levels at 10% for p53 and topoII alpha, and 5% for MAPK. The Ki67 immunoexpression was assessed by means of Olympus Image Analysis System as a percentage of immunopositive cells in 1000 tumor cells. KRAS and BRAF mutational analysis was performed on 73 available microdissected samples. Results Of 81 cases of OSCs 13.6% were of low-grade and 86.4% were of high-grade morphology. In the high-grade group there was a significantly higher immunoexpression of p53 (P < 0.001) and topoII alpha (P = 0.001), with Ki67 median 56.5 vs. 19 in low-grade group (P < 0.001). The difference in immunoexpression of active MAPK between low- and high-grade group was also significant (P = 0.003). MAPK positive immunostaining was detected in 63.6% of low-grade vs. 17.1% of high-grade OSCs. The frequency of KRAS mutation was significantly higher in low-grade as compared to high-grade group (P = 0.006). None of the samples had BRAF mutation. In addition, we detected positive MAPK immunoexpression in 13/59 samples with wild-type KRAS, suggesting that activation of MAPK pathway is not ultimately related either to KRAS or BRAF mutation. Seven morphologically high-grade samples (11.7%) showed both KRAS mutation and p53 immunopositivity. Conclusions Although this study is limited by its humble number of low-grade samples, our data fit the proposed dualistic pathway of ovarian carcinogenesis. Mutational analysis for KRAS and BRAF discloses some possible interactions between different tumorigenic pathways of low- and high-grade carcinomas. Immunohistochemical staining for MAPK was not sufficiently sensitive, nor specific, to precisely predict the KRAS mutation. However, it appears to be quite reliable in ruling out a KRAS mutation if the staining is negative. Virtual Slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/9283563368804632 Zusammenfassung Hintergrund Wir untersuchten die Immunohistochemische Expression der p53, MAPK, topoisomerase II alpha (topoII alpha) und Ki67 in Ovarialkarzinomen (OSCs) anbei mit Mutationsanalyse für KRAS und BRAF. Methode 81 OSCs Fälle wurden analysiert und Immunohistochemisch untersucht mit Antikörper gegen p53, MAPK, topoII alpha und Ki67. Die Färbung war ausgewertet als der Prozent von immunopositiven Zellen mit den "cut-of" Niveau an 10% für p53 und topoII alpha und 5% für MAPK. Die Ki67 Expression war bewertet mittels Olympus Image Analysis System als der Prozent von immunopositiven Zellen in 1000 Tumorzellen. KRAS and BRAF Mutationsanalyse wurde in 73 verfügbaren microdissections Stichproben aufgeführt. Ergebnisse Von 81 OSCs Fälle 13.6% zeigte "low-grade" und 86.4% "high-grade" Morphologie. In der "high-grade" Gruppe war eine statistisch bedeutende höhere Expression von p53 (P < 0.001) und topoII alpha (P = 0.001) mit Ki67 median von 56.5 im Gegensatz zu 19 in der "low-grade" Gruppe (P < 0.001). Die Differenz in Immunoexpression von aktiver MAPK zwischen der "low-grade" und "high-grade" Gruppe war statistisch bedeutend (P = 0.003). MAPK positive Expression war in 63.6% der "low-grade" im Gegensatz von 17.1% der "high-grade" Karzinoms bemerkt. Die Häufigkeit der KRAS Mutation war bedeutend höher in "low-grade" im Verglich zu der "high-grade" Gruppe (P = 0.006). Keiner der Stichproben hate BRAF Mutation. Wir haben auch eine positive MAPK Expression in 13/59 der Stichproben mit "wild-type" KRAS bemerkt, was sugeriert das die Aktivation des MAPK Pfads ist nicht letztmalig mit KRAS oder BRAF verbunden. Sieben der "high-grade" Stichproben (11.7%) waren KRAS Mutation und p53 Expression positive. Schlussworte Obwohl diese Studie mit bescheiden Nummer von "low-grade" Stichproben limitiert ist, unsere Daten passen in das dualistische Modell von Ovarial Karzinogenesis. Mutationsanalyse für KRAS und BRAF enthüllen einige mögliche Interaktionen zwischen verschieden tumorigenen Wege von "low"- and "high-grade" Karcinomen. Die Immunohistochemische Expression für MAPK war nicht empfindlich oder spezifisch genüg um den KRAS mutations Status des Tumor genau vorauszusagen. Es scheint das die MAPK Expression ziemlich verlässlich ist in ausschließen der KRAS Mutation, wenn die Expression negative ist.